Assessing the Drosophila melanogaster and Anopheles gambiae Genome Annotations Using Genome-Wide Sequence Comparisons - Jaillon, Olivier (Cold Spring Harbor Laboratory Press, 2003)
We performed genome-wide sequence comparisons at the protein coding level between the genome sequences of Drosophila melanogaster and Anopheles gambiae. Such comparisons detect evolutionarily conserved regions (ecores) that can be used for a qualitative and quantitative evaluation of the available annotations of both genomes. They also provide novel candidate features for annotation. The percentage of ecores mapping outside annotations in the A. gambiae genome is about fourfold higher than in D. melanogaster. The A. gambiae genome assembly also contains a high proportion of duplicated ecores, possibly resulting from artefactual sequence duplications in the genome assembly. The occurrence of 4063 ecores in the D. melanogaster genome outside annotations suggests that some genes are not yet or only partially annotated. The present work illustrates the power of comparative genomics approaches towards an exhaustive and accurate establishment of gene models and gene catalogues in insect genomes.